Mathematical Model of Heat Transfer, Cooling Mass and Storage Time of Apples (Malus domestica) in Packaging - Yohanes Setiyo, Bambang Admadi Harsojuwono , Ida Bagus Wayan Gunam, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The cooling of fruit at high relative humidity can control respiration, moisture loss, ripening, and the action of enzymes and microorganisms that cause spoilage and decrease shelf life. A mathematical model was developed for cooling or storing packaged apples and solved with finite elements predicting one-dimensional heat and mass transfer. The model consists of two separate parts of the heat and mass transfer model, namely to predict air humidity, air condensation, and moisture content. The temperature predicted by the model for refrigeration or storage simulations is compared with the experimentally secermined temperature.Validity test and sensitivity test were used to test the validity of the mathematical model of heat transfer and mass transfer during cooling or storage of apples. Scatter plot test, residual test, and validity test to secermine the validity of the developed mathematical model. This model is successful in estimating the time-temperature profile at various locations in bulk apples packaging during the cooling process and the storage process